Isoflurane anesthesia alters 31P magnetic resonance spectroscopy markers compared to awake mouse brain - Saba Molhemi; Rasmus West Knopper; Christian Stald Skoven; Thomas Beck Lindhardt; Caroline Degel; Leif Østergaard; Brian Hansen (PLoS ONE, 2025)
Normal brain function hinges on energy-intensive processes. Consequently, alterations to the brain’s metabolic state are common hallmarks in several pathological conditions. Phosphorus Magnetic Resonance Spectroscopy ( 31 P MRS) is a noninvasive method for measuring key markers of brain energy metabolism, including adenosine triphosphate (ATP), inorganic phosphate (Pi), and phosphocreatine (PCr), as well as markers for cell membrane phospholipid turnover, phosphomonoester (PME) and phosphodiester (PDE). Preclinical rodent 31 P MRS has so far been done under anesthesia - with isoflurane being one of the most commonly used anesthetic agents. The use of isoflurane in 31 P MRS is a concern, as anesthetics are known to affect neuronal activity and energy metabolism in the brain. Its use therefore comes with a risk of perturbing brain physiology. Awake mouse MRS avoids this and allows the effect of isoflurane to be quantified. Thus, we here compare mouse brain 31 P MRS in awake MR-habituated mice and isoflurane anesthesia. We find that 31 P metabolite levels differ between the awake state and isoflurane anesthesia in mice. Our findings show that low-dose isoflurane anesthesia reduces PCr levels in the mouse brain and is accompanied by decreases in intracellular pH and decreased PME levels.